(untitled) (Scientific journal of the Fergana State University, 2026)
This study investigates the formation of developed surface modification of molybdenum foils through electrochemical anodization in oxalic acid and picosecond pulsed laser irradiation. The resulting surface morphology, elemental composition, and crystallinity were analysed using SEM, EDS, and XRD methods. Anodization process produced a rough, none-uniform surfaces, while laser treatment achieved uniform micro-crystalline arrays. Advanced surface and micro-crystalline arrays by pulsed laser irradiation will open new ways in the field of catalytic applications.